Pre-migration traumatic experiences, post-migration perceived discrimination and substance use among Russian and Kurdish migrants-a population-based study - Essi S. Salama; Anu E. Castaneda; Eero Lilja; Jaana Suvisaari; Shadia Rask; Tiina Laatikainen; Solja Niemelä (WILEY, 2022)
Background and aims
The associations between traumatic events, substance use and perceived discrimination have been rarely studied among migrants in host countries. We examined whether pre‐migration potentially traumatic experiences (PTEs) or perceived discrimination (PD) are associated with substance use among migrants with voluntary (Russians) and forced (Kurds) migration backgrounds.
Design
Cross‐sectional interview and health examination data from the Finnish Migrant Health and Wellbeing Study were used. The target sample (n = 1000 for each group) was drawn from the national population register using stratified random sampling by participants’ country of birth and native language.
Setting
Population‐based data were collected from six cities in Finland during 2010–12.
Participants
The participation rates were 68% (Russians) and 59% (Kurds). The analytical sample size varied (Russians n = 442–687, Kurds n = 459–613), as some participants completed only interview, health examination or short interview. The majority of Kurds had a refugee background (75%) while Russians had mainly migrated for other reasons (99%).
Measurements
The three main outcomes were self‐reported binge drinking, daily smoking and life‐time cannabis use. PTEs and PD were self‐reported in the interview. Socio‐demographic background, migration‐related factors and current affective symptoms were adjusted for.
Findings
Among Kurds, PTEs were associated with binge drinking [adjusted odds ratio (aOR) = 2.65, 95% confidence interval (CI) = 1.30–5.42] and PD was associated with life‐time cannabis use (aOR = 3.89, 95% CI = 1.38–10.97) after adjusting for contextual factors. Among Russians, PTEs were associated with life‐time cannabis use adjusting for contextual factors (aOR = 2.17, 95% CI = 1.12–4.18).
Conclusions
In Finland, pre‐migration traumatic experiences appear to be associated with life‐time cannabis use among the Russian migrant population (voluntary migration) and binge drinking among the Kurdish migrant population (forced migration). Perceived discrimination in Finland appears to be associated with life‐time cannabis use among Kurdish migrants.